Altered expression of immune factors in sevenband grouper, Hyporthodus septemfasciatus following nervous necrosis virus challenge at optimal and suboptimal temperatures. Issue 119 (December 2021) - Krishnan, Rahul; Jang, Yo-Seb; Kim, Jong-Oh; Oh, Myung-Joo
Abstract: The nervous necrosis virus (NNV) infection is generally observed in aquafarms when the seawater temperature is higher than 24 °C and the fishes seem to be refractory to disease at suboptimal temperatures below 20 °C suggesting a role of thermoregulation in NNV pathogenesis. The present study profiled the temperature-dependent regulation of cytokines (TNF-α, IL-1β and IFN-γ), innate antiviral factors (IFN-1, Mx, ISG-15), adaptive immune factors (CD-4, CD-8, IgM), signaling regulators (SOCS-1, SOCS-3), transcription factors (STAT-1, STAT-3) and microglial and NCC/NK specific cell markers (TMEM-119 and NCCRP-1) during NNV challenge in seven-band grouper, Hyporthodus septemfasciatus . The co-habitation challenge at 17 °C with showed a sustained expression of proinflammatory cytokines and following rechallenge with a dose of 10 4 TCID50 /100μL/fish at optimal temperature, the survivors also exhibited a stable expression of immune factors. The 100% survival following the challenge at sub-optimal (17 °C) and rechallenge at optimal (25 °C) was due to the stable and sustained activation of the immune response. However, at 25 °C, the rechallenge displayed a priming effect with hyperactivation of the immune system evident from the immune gene expression profile. The mortality pattern observed is co-related with the cytokine storm as is evident from the gene expression profile. Whereas, neither of the adaptive immune markers was suggestive of humoral immune response in the 17 °C groups. Also, the data suggest a possible role of NK cell and microglia in mediating antiviral immune response following infection in the brain at different temperatures, where, former is beneficial in restricting viral infection with higher host tolerance. Highlights: The challenge at 17 °C showed a sustained expression of proinflammatory cytokines. At 25 °C, the rechallenge displayed a priming effect displaying a hyperactivation of the immune system. Neuropathology associated with NNV infection at optimal temperature is a function of aberrant cytokine storm. Protective immunity observed at suboptimal temperature is mediated by non-cytolytic clearance.